Wildlife value orientations among diverse audiences in the American Southwest: helping state wildlife agencies broaden their constituent base - Chase, Loren, author; Teel, Tara, advisor; Manfredo, Mike, advisor; Bruyere, Brett, committee member; Boone, Randall, committee member (Colorado State University. Libraries, 2013)
There is growing recognition among wildlife professionals in the United States that although their decisions largely focus on topics biological in nature, the social, political, and economic ramifications of these decisions are considerable as well. As a result, social science is increasingly being included in the wildlife management decision-making process. At the same time, the constituencies that entrust state wildlife management agencies are diversifying, in terms of both their cultural heritage and their wildlife-related interests. To improve the effectiveness of agency efforts aimed at maintaining support from long-established stakeholders while simultaneously embracing emerging publics, there is a need to better understand the characteristics of diverse audiences. Wildlife value orientation (WVOs) theory offers an advantageous framework for systematically understanding the wildlife-related beliefs and interests of various segments of society. This dissertation investigates WVOs and their application across three diverse spectra: culture, methodology, and generations, each addressed in its own manuscript and through research conducted as part of a series of case studies occurring in Arizona. In Chapter II, WVOs are compared across cultures; specifically, this chapter explores possible differences and similarities in WVOs between Latinos and Caucasians. In addition to measuring WVOs, this study collected information about life values, wildlife-related attitudes, subjective norms, and behavioral intentions. Results indicated that Latinos perceive wildlife differently than Caucasians; however there was significant heterogeneity within Latino communities in the way they interacted with and related to wildlife. These findings provide managerial insight into engaging Latino communities in wildlife conservation issues as well as offer theoretical contributions by expanding the application of the WVO concept cross-culturally. In Chapter III, we introduce and test a mixed methods approach for measuring WVOs within Latino communities. As agencies are increasingly charged with managing wildlife for a broader clientele, including people of diverse demographic and cultural backgrounds, it raises questions about the potential limitations of traditional survey methodologies for cross-cultural WVO assessment. In the interest of addressing this concern we examined WVOs in Latino communities in Arizona using two quantitative and two qualitative methodologies. We found evidence that traditional quantitative WVO surveys may still be reliable for diverse audiences; however, we also identify scenarios wherein other methodologies may be advantageous. In Chapter IV, WVOs are compared across generations. As various cohorts of people across time experience different societal conditions believed to play a role in WVO formation, they can be grouped according to similar formative experiences. These generations experience various levels of urbanization, affluence, education, and technology, all contributing to distinctive life values. Concurrent with modernization is a value shift that is altering the way people perceive and interact with wildlife, specifically increasing the egalitarian perception that wildlife may serve as potential companions capable of trusting relationships with humans and who deserve caring and rights similar to those of humans. We confirmed there is a differential in the way generations perceive wildlife, suggesting agencies may want to consider engaging each cohort differently, according to how they relate to wildlife. These findings may assist agencies as they continue to engage broader constituencies and attempt to remain salient to younger generations. Overall, we found WVO theory to be a functional and robust framework for examining people's perceptions of wildlife across cultures, methodologies, and generations. Because of its durability, WVO theory shows promise for unifying research on human-wildlife relationships in a way that transcends space, time, and contextual situations. Additionally, WVOs have the practical utility of helping agencies understand the social context of wildlife conservation, and may assist agencies in comprehending changing societal conditions so they may be better prepared for the future of wildlife conservation.
Keywords: human dimensions; wildlife; measurement; age; Latinos; wildlife value orientations